Beyond Digital Flexibility - David du Toit; Ngubeni Phumzile (Clinical Sociology Review)
This qualitative study explores the experiences of food-delivery couriers employed by UberEats, MrDFood and BoltFood in Johannesburg, South Africa. Through in-depth interviews with Black African male migrant food delivery couriers from Zimbabwe, Malawi and Uganda, the study investigates the opportunities, challenges and coping strategies characterising their work in the gig economy. Key findings reveal increased earning potential, multiple job opportunities and flexible schedules as the main benefits. However, food delivery couriers also experience challenges including crime and safety risks, lack of fringe benefits, customer harassment, and rising petrol and data costs. To cope with these challenges, food delivery couriers utilise several individual strategies such as WhatsApp support groups and networks to help them with job-related challenges. The article concludes with several interventions to policy change to improve the working conditions of food delivery couriers.